Ergonomia e design: redesenhar produtos para a prática de artes marcias - Rodrigues, Luan Gustavo (2011)
This paper proposes a historical survey of kimono karate by presenting the evolution of Nipponese clothing into what has generated the uniform for fighting. The objective has been based on the damage caused to the athletes bodies due to discomfort from excessive sweating. For the redesign of the uniform, the ergonomic made use of the technological advances in the textile manufacturing. This is a case studied in the fashion design field with literature support, besides methods of deductive, inductive, hypothetical-deductive and statistical approaches, applied to the Kimonos Shiroi company, an important organization from the department of sportive clothing located at Apucarana-PR.